Pengaruh Edukasi Menggunakan Masker Melalui Media Video Animasi Terhadap Perilaku Pedagang Pasar Panorama Di Wilayah Kota Bengkulu - Septiyanti Septiyanti; Harum Maulidia Ningsih; Husni Husni; Ahmad Rizal (Poltekkes Kemenkes Bengkulu, 2022)
Corona virus disease (COVID-19) is an infectious disease and is caused by a new variant of the corona virus discovered in 2019 that can cause disease in humans and animals. The COVID-19 pandemic is a case that is troubling the world because the number of confirmed cases that result in deaths continues to increase and spread to various countries. Corona virus is transmitted by droplets from infected people and one way to prevent transmission is to use a mask. Traditional markets are places that have the potential to spread the virus. A survey conducted at the Panorama market in Bengkulu City shows the low awareness of market traders in using masks. The purpose of the study was to determine the effect of animated video education on the behavior of using masks on traders in the Panorama Market, Bengkulu City. This study used a quasi-experimental research design with a pre-post design with a control group. The number of samples in this study amounted to 30 people, consisting of the intervention group 15 people and the control group 15 people. Sampling using purposive sampling technique. The results showed that the average knowledge increased from 61.33 to 88.00, attitudes from 23.40 to 35.47 and actions from 48.00 to 85.33 after being given animation video media education with a p value of 0.000.